Induction of ferroptotic cell death for overcoming cisplatin resistance of head and neck cancer. Issue 1 (10th October 2016) - Roh, Jong-Lyel; Kim, Eun Hye; Jang, Hye Jin; Park, Jin Young; Shin, Daiha
Highlights: Cystine starvation or glutamine excess leads to ferroptosis in head and neck cancer (HNC) cells. Inhibition of cystine/glutamate antiporter (SLC7A11) induces ferroptosis in cisplatin-resistant HNC cells. Silencing of the SLC7A11 gene increases the cisplatin sensitivity of resistant HNC cells. Sulfasalazine sensitizes cisplatin-resistant HNC cells to cisplatin in vitro and in vivo . Abstract: Inhibition of key molecules related to ferroptosis, cystine/glutamate antiporter and glutathione peroxidase, may induce eradication of chemotherapy/radiotherapy-resistant cancer cells. The present study investigated whether ferroptosis could overcome head and neck cancer (HNC) resistance to cisplatin treatment. Three cisplatin-resistant HNC cell lines (AMC-HN3R, -HN4R, and -HN9R) and their parental lines were used. The effects of cystine and glutamate alteration and pharmacological and genetic inhibition of cystine/glutamate antiporter were assessed by measuring viability, death, reactive oxygen species production, protein expression, and preclinical mouse tumor xenograft models. Conditioned media with no cystine or glutamine excess induced ferroptosis of both cisplatin-sensitive and -resistant HNC cells without any apparent changes to necrosis and apoptosis markers. The cystine/glutamate antiporter inhibitors erastin and sulfasalazine inhibited HNC cell growth and accumulated lipid reactive oxygen species, thereby inducing ferroptosis. Genetic silencing of cystine/glutamate antiporter with siRNA or shRNA treatment also induced effective ferroptotic cell death of resistant HNC cells and enhanced the cisplatin cytotoxicity of resistant HNC cells. Pharmacological and genetic inhibition of cystine/glutamate antiporter significantly sensitized resistant HNC cells to cisplatin in vitro and in vivo . Pharmacological and genetic inhibition of cystine/glutamate antiporter overcomes the cisplatin resistance of HNC cells by inducing ferroptosis.